Play Therapy in Residential Treatment Centers for Children. Issue 4 (2nd October 2019) - Agarwal, Sarah M.; Ray, Dee C.
ABSTRACT: Residential Treatment Centers (RTCs) serve youth who have suffered extreme abuse and trauma and must reside in 24-hour facilities to receive mental health, medication, and social services. Currently, specific therapeutic interventions utilize talk therapy or cognitive therapies, which may have limited use with children due to developmental considerations, specifically children who have been through trauma that has affected their development. Child-Centered Play Therapy (CCPT) is introduced as an evidence-based expressive therapy modality that emphasizes the child's natural language of play as a way to support emotional and psychological healing. This article discusses limitations to residential treatment center research as well as ways to implement play therapy into residential treatment settings for children who are in need of such services through the use of brief play therapy, group play therapy, and Child Parent Relationship Therapy (CPRT).